Islamic Versus Conventional Banking: An Insight into the Malaysian Dual Banking System - Ali, Khurshid; Khan, Zeeshan; Saleh, Abdullah (Asian Journal of Economics and Empirical Research, 2016)
This research aims at examining to match the performance of both Malaysian Islamic and conventional banking through profitability, efficiency, solvency and liquidity and risk management ratios using independent t-test and discriminant regression models. Fifteen financial ratios are applied to examine the competitiveness of the both industries created on the financial data of ten Malaysian banks, five from both industries, over the period of six financial years (2009-2015). According to the independent t-test descriptive statistics, the result finds that conventional banks perform well than Islamic banks in the context profitability and efficacy ratios. Nevertheless, in terms of solvency and liquidity & risk management ratios Islamic banks outperform conventional banks operating in Malaysia. Further, it has been revealed by the disciriminant analysis that in general conventional banks execute well than Islamic banks operating in Malaysia when it comes to the profitability, solvency, efficiency and liquidity & risk management ratios.